The Impact of AI Chatbots, Service Personalization, and Response Speed ​​on Customer Satisfaction in E-Commerce in Indonesia - Rini Hadiyati; Feba Dinova Dex Tovtora S (West Science Interdisciplinary Studies, 2025)
This study investigates the impact of AI chatbots, service personalization, and response speed on customer satisfaction in the e-commerce sector in Indonesia. As e-commerce platforms continue to grow, customer satisfaction has become a critical factor in maintaining competitiveness. A quantitative approach was employed, utilizing a structured questionnaire to gather data from 175 respondents. The data were analyzed using multiple regression analysis through SPSS version 25. The results indicated that AI chatbots, service personalization, and response speed all have a significant positive impact on customer satisfaction, with response speed having the strongest influence. These findings suggest that optimizing AI chatbot functionalities, enhancing personalized experiences, and improving response speed are essential strategies for e-commerce businesses aiming to enhance customer satisfaction. This study provides valuable insights for e-commerce practitioners in Indonesia and contributes to the literature on customer service in digital platforms.